Colonic inflammation affects myenteric alpha-synuclein in nonhuman primates - Resnikoff H; Metzger JM; Lopez M; Bondarenko V; Mejia A; Simmons HA; Emborg ME (Dove Medical Press, 2019)
Henry Resnikoff,1 Jeanette M Metzger,1,2 Mary Lopez,1 Viktoriya Bondarenko,1 Andres Mejia,1 Heather A Simmons,1 Marina E Emborg1–31Preclinical Parkinson’s Research Program, Wisconsin National Primate Research Center, University of Wisconsin – Madison, Madison, WI, USA; 2Cellular and Molecular Pathology Graduate Program, University of Wisconsin – Madison, Madison, WI, USA; 3Department of Medical Physics, University of Wisconsin – Madison, Madison, WI, USABackground: Parkinson’s disease (PD) patients frequently present gastrointestinal (GI) dysfunction that, in many cases, predates the onset of motor symptoms. In PD, the presynaptic protein alpha-synuclein (α-syn) undergoes pathological changes, including phosphorylation and aggregation leading to the formation of Lewy bodies, which can be found in neurons of the enteric nervous system (ENS). Inflammation has been proposed as a possible trigger of α-syn pathology. Interestingly, patients with inflammatory bowel disease and irritable bowel syndrome, conditions associated with GI inflammation, are at higher risk of developing PD. Captive common marmosets (Callithrix jacchus) develop colitis, providing a natural platform to assess the relationship between α-syn pathology and GI inflammation.Materials and Methods: Sections of proximal colon from marmosets with colitis (n=5; 5.3±2.3 years old; 4 male) and normal controls (n=5; 4.1±1.6 years old; 1 male) were immunostained against protein gene product 9.5 (PGP9.5), human leukocyte antigen DR (HLA-DR), cluster of differentiation 3 (CD3), cluster of differentiation 20 (CD20), glial fibrillary acidic protein (GFAP), 8-hydroxy-2’-deoxyguanosine (8-OHdG), α-syn, and serine 129 phosphorylated α-syn (p-α-syn). Immunoreactivity of each staining in the myenteric plexus was quantified using NIH ImageJ software.Results: Marmosets with colitis had significantly increased expression of inflammatory markers (HLA-DR, p<0.02; CD3, p<0.008), oxidative stress (8-OHdG, p<0.05), and p-α-syn (p<0.02) and decreased expression of α-syn (p<0.04) in the colonic myenteric ganglia compared to normal, healthy controls.Conclusion: Colonic inflammation is associated with changes in α-syn expression and phosphorylation in the myenteric plexus of common marmosets. Future evaluation of the vagus nerve and brain of animals with colitis will be key to assess the contribution of colitis-induced ENS α-syn pathology to PD-like pathology in the brain.Keywords: Lewy bodies, common marmosets, colitis, Parkinson’s disease, phosphorylated alpha-synuclein, HLA-DR